Bisphenol A exposure enhances proliferation and tumorigenesis of papillary thyroid carcinoma through ROS generation and activation of NOX4 signaling pathways - Yi Wang; Xuling Su; Qianqian Wang; Likun Zhang; Yaling Yu; Yiwei Zhao; Zhiyan Liu (Ecotoxicology and Environmental Safety)
As a prevalent industrial material and component of consumer products, bisphenol A (BPA) is linked to hormone homeostasis disruption and potential carcinogenicity. However, the precise mechanisms through which BPA contributes to thyroid carcinogenesis, especially in papillary thyroid carcinoma (PTC), are not fully understood. This study investigates how BPA boosts the proliferation and tumorigenic characteristics of thyroid cells. BPA exposure significantly increased cell proliferation in a duration-dependent manner at a concentration of 0.5 μM, which is slightly higher than human exposure levels. Therefore, this study utilized BPA treatment concentrations of 0.1 µM and 0.5 µM. BPA augmented the invasiveness of PTC cells with a dependency on both dosage and temporal factors. RNA-seq and gene expression analysis from normal human thyroid follicular epithelial cells suggested that BPA upregulated genes related to oxidative stress and thyroid cancer. Concurrently, our study revealed significant upregulation of NOX4 in thyroid tumors compared to normal thyroid tissues, with higher expression levels observed in advanced carcinomas by analyses of the TCGA database. BPA induces the upregulation of NOX4 in human thyroid cells, thereby triggering the activation of MAPK and PI3K/AKT pathways. In xenograft models, BPA treatment resulted in increased tumor size and Ki-67 proliferation index, accompanied by upregulated NOX4 expression. Additionally, BPA exposure led to higher levels of free triiodothyronine (FT3), indicating thyroid hormone disruption. Mechanistically, BPA activates the MAPK and PI3K/AKT pathways via NOX4, leading to increased ROS production and cell proliferation. This was further demonstrated through the use of ROS scavenger treatment and si-NOX4, which showed that BPA stimulates ROS generation by activating NOX4/MAPK and NOX4/PI3K/AKT pathways in thyroid cells. This finding enhances our understanding of the pathogenesis of PTC related to BPA exposure and highlights the necessity for rigorous health risk assessments regarding BPA exposure.